A 20-Year Review of Biomechanical Experimental Studies on Spine Implants Used for Percutaneous Surgical Repair of Vertebral Compression Fractures. (21st September 2022) - Gajavelli, Sairam; Gee, Aaron; Bagheri, Z. Shaghayegh; Schemitsch, Emil H.; Bailey, Christopher S.; Rasoulinejad, Parham; Zdero, Radovan
Abstract : A vertebral compression fracture (VCF) is an injury to a vertebra of the spine affecting the cortical walls and/or middle cancellous section. The most common risk factor for a VCF is osteoporosis, thus predisposing the elderly and postmenopausal women to this injury. Clinical consequences include loss of vertebral height, kyphotic deformity, altered stance, back pain, reduced mobility, reduced abdominal space, and reduced thoracic space, as well as early mortality. To restore vertebral mechanical stability, overall spine function, and patient quality of life, the original percutaneous surgical intervention has been vertebroplasty, whereby bone cement is injected into the affected vertebra. Because vertebroplasty cannot fully restore vertebral height, newer surgical techniques have been developed, such as kyphoplasty, stents, jacks, coils, and cubes. But, relatively few studies have experimentally assessed the biomechanical performance of these newer procedures. This article reviews over 20 years of scientific literature that has experimentally evaluated the biomechanics of percutaneous VCF repair methods. Specifically, this article describes the basic operating principles of the repair methods, the study protocols used to experimentally assess their biomechanical performance, and the actual biomechanical data measured, as well as giving a number of recommendations for future research directions.